Carbonaceous-coated graphite particles, negative electrode for lithium ion secondary batteries, lithium ion secondary battery, and method for producing carbonaceous-coated graphite particles

By optimizing the firing conditions of carbon-coated graphite particles, the problems of insufficient output characteristics, fast charging characteristics and cycle characteristics of lithium-ion secondary batteries in automotive applications are solved, and multiple performance improvements of the negative electrode materials of lithium-ion secondary batteries are achieved. .

CN119317598APending Publication Date: 2025-01-14JFE CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480002875.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-06
Filing Date
2024-02-28
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries require excellent output characteristics, fast charging characteristics and cycle characteristics in automotive applications, but the prior art is difficult to meet these needs at the same time.

Method used

By optimizing the firing conditions of carbonaceous coated graphite particles, ensuring that the surface carbonaceous substance of graphite particles has specific crystallinity. The specific method includes heating in a water vapor atmosphere, controlling the starting temperature to reduce the starting temperature between 800 and 980°C, and passing The non-oxidizing gas atmosphere and the oxidizing gas atmosphere are alternately exposed, and a multi-stage sintering treatment is carried out.

Benefits of technology

It has achieved excellent output characteristics, fast charging characteristics and cycle characteristics of the negative electrode material of lithium-ion secondary battery, and is suitable for battery needs of hybrid vehicles and electric vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166905870000191
    Figure BDA0005166905870000191
  • Figure HDA0005166905890000011
    Figure HDA0005166905890000011
Patent Text Reader

Abstract

Provided are carbonaceous-coated graphite particles having excellent output characteristics, fast charge characteristics, and cycle characteristics when used as a negative electrode material for a lithium ion secondary battery. The carbonaceous-coated graphite particles comprise graphite particles and carbonaceous that coats at least a portion of the surfaces of the graphite particles, the mass reduction initiation temperature when heated in a water vapor atmosphere is 800-980 DEG C, and the content of the carbonaceous is 0.1-15.0 parts by mass per 100.0 parts by mass of the graphite particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to carbonaceous coated graphite particles, a negative electrode for a lithium ion secondary battery, a lithium ion secondary battery and a method for producing the carbonaceous coated graphite particles. Background Art

[0002] A lithium-ion secondary battery has a negative electrode, a positive electrode, and a non-aqueous electrolyte as main components, and functions as a secondary battery by allowing lithium ions to move between the negative electrode and the positive electrode during discharge and charge processes.

[0003] Conventionally, carbon-coated graphite particles in which the surface of graphite particles is coated with carbon are sometimes used as negative electrode materials for lithium-ion secondary batteries (Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2021 / 260964 Summary of the invention

[0007] Problems to be solved by the invention

[0008] It is expected that lithium-ion secondary batteries will be installed in large quantities in automobiles (hybrid vehicles, electric vehicles, etc.) in the future.

[0009] For example, in hybrid vehicles, since acceleration is important, a battery having excellent output characteristics (rapid discharge characteristics) is required.

[0010] Furthermore, in electric vehicles, there is a demand for batteries that are excellent in rapid charging characteristics and whose capacity is not easily degraded even when repeatedly charged and discharged (that is, have excellent cycle characteristics).

[0011] Therefore, an object of the present invention is to provide carbonaceous coated graphite particles which are excellent in output characteristics, rapid charging characteristics, and cycle characteristics when used as a negative electrode material for a lithium ion secondary battery.

[0012] Solutions to the problem

[0013] As a result of intensive studies, the present inventors have found that carbonaceous material having specific crystallinity can be obtained by optimizing the calcination conditions when producing carbonaceous coated graphite particles. As a result, the above-mentioned object can be achieved, thereby completing the present invention.

[0014] That is, the present invention provides the following [1] to [5].

[0015] [1] A carbonaceous coated graphite particle comprising:

[0016] Graphite particles, and

[0017] a carbonaceous material covering at least a portion of the surface of the graphite particles;

[0018] The mass reduction starting temperature when heated in a water vapor atmosphere is 800 to 980° C., and the content of the carbonaceous material is 0.1 to 15.0 parts by mass based on 100.0 parts by mass of the graphite particles.

[0019] [2] The carbonaceous coated graphite particles according to [1] above, which are a negative electrode material for a lithium ion secondary battery.

[0020] [3] A negative electrode for a lithium ion secondary battery, comprising the carbonaceous coated graphite particles according to [1] above.

[0021] [4] A lithium ion secondary battery comprising the negative electrode described in [3].

[0022] [5] A method for producing carbonaceous coated graphite particles, the method being a method for producing the carbonaceous coated graphite particles described in [1] above, the method comprising:

[0023] making a carbonaceous precursor, which is a precursor of the carbonaceous material, adhere to the graphite particles to obtain precursor-attached graphite particles,

[0024] A first calcination step is performed in which the precursor-attached graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. in a non-oxidizing gas atmosphere.

[0025] After the first calcination, an intermediate exposure is performed in which the precursor-attached graphite particles are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C.

[0026] After the intermediate exposure, a second calcination is performed in which the precursor-attached graphite particles are heated at a temperature of 1100 to 1500° C. in a non-oxidizing gas atmosphere.

[0027] Effects of the Invention

[0028] According to the present invention, it is possible to provide carbonaceous coated graphite particles which are excellent in output characteristics, rapid charging characteristics, and cycle characteristics when used as a negative electrode material for a lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a cross-sectional view of an evaluation battery produced to evaluate battery characteristics in Examples and Comparative Examples.

[0030] Explanation of symbols

[0031] 1: External cup

[0032] 2: Negative electrode

[0033] 3: External can

[0034] 4: Positive electrode

[0035] 5: Partition

[0036] 6: Insulation pad

[0037] 7a: Current collector

[0038] 7b: Current Collector DETAILED DESCRIPTION

[0039] In this specification, when "to" is used to express a range, the range includes both ends of "to". For example, the range of A to B includes A and B.

[0040] [Carbon coated graphite particles]

[0041] The carbonaceous coated graphite particles of the present embodiment (hereinafter also referred to as "the present carbonaceous coated graphite particles") comprise: graphite particles, and carbonaceous material coating at least a portion of the surface of the above-mentioned graphite particles, wherein the mass reduction starting temperature when heated in a water vapor atmosphere is 800 to 980°C, and the content of the above-mentioned carbonaceous material is 0.1 to 15.0 parts by mass relative to 100.0 parts by mass of the above-mentioned graphite particles.

[0042] When the present carbonaceous coated graphite particles are used as a negative electrode material for a lithium ion secondary battery, they are excellent in output characteristics, rapid charging characteristics, and cycle characteristics.

[0043] 〈Mass reduction starting temperature〉

[0044] The mass reduction starting temperature when the carbonaceous coated graphite particles are heated in a water vapor atmosphere (also simply referred to as "mass reduction starting temperature") reflects the crystallinity of the carbonaceous material coating the graphite particles. The higher the mass reduction starting temperature, the higher the crystallinity.

[0045] The mass reduction starting temperature is 800°C or higher, preferably 840°C or higher, and more preferably 880°C or higher. As a result, the rapid charging characteristics and output characteristics are excellent. This is because the higher the crystallinity of the carbonaceous material covering the graphite particles, the higher the conductivity of lithium ions and electrons.

[0046] On the other hand, when the mass reduction start temperature is too high, the carbonaceous crystals grow excessively. In this case, the grain boundaries are reduced, and with this, the paths for diffusing lithium ions to the carbonaceous are reduced, so the fast charging characteristics and output characteristics deteriorate. Therefore, the mass reduction start temperature is preferably below 980°C, more preferably below 950°C, and further preferably below 935°C.

[0047] The mass reduction starting temperature is determined as follows.

[0048] First, the carbonaceous coated graphite particles were heated in a water vapor atmosphere. More specifically, thermogravimetric analysis was performed under the following conditions to obtain a graph showing the relationship between the mass reduction rate and the temperature.

[0049] Thermogravimetric analysis was performed under the following conditions.

[0050] ·Equipment: Steam gasification carbon analysis device CASGa (manufactured by Rigaku Corporation)

[0051] Gas atmosphere: 20% water vapor-N2 balance (water vapor partial pressure P H2O =20.2kPa)

[0052] Heating speed: 10℃ / min

[0053] ·Measurement method: Speed-controlled thermogravimetric analysis (speed control value: 0.001% / second)

[0054] Next, the temperature at which the mass reduction rate is 0.50% is read from the obtained graph (mass reduction rate-temperature graph), and this temperature is determined as the mass reduction start temperature.

[0055] The reason why the thermogravimetric analysis is performed in a water vapor atmosphere is as follows.

[0056] Carbon is oxidized by oxidants such as oxygen, carbon dioxide and water vapor at high temperatures to become carbon dioxide or carbon monoxide gas.

[0057] At this time, the mass reduction start temperature of carbon varies depending on the type of oxidant and the crystallinity of carbon oxidized by the oxidant. In other words, when the gas atmosphere around carbon is not constant during thermogravimetric analysis, the mass reduction start temperature cannot be correlated with the crystallinity of carbon.

[0058] Among the above-mentioned oxidizing agents, water vapor is most suitable for evaluating the crystallinity of carbon from the viewpoints of ease of handling, purity, concentration control, and the like.

[0059] Therefore, the gas atmosphere around carbon during thermogravimetric analysis is set to a water vapor atmosphere. This allows the mass loss start temperature to be correlated with the crystallinity of carbon.

[0060] 〈Carbon content〉

[0061] For the reason of excellent cycle characteristics, the content of carbon is 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and more preferably 0.5 parts by mass or more, based on 100.0 parts by mass of the graphite particles.

[0062] On the other hand, for the reason of excellent rapid charging characteristics and output characteristics, the carbon content is 15.0 parts by mass or less, preferably 10.0 parts by mass or less, more preferably 8.0 parts by mass or less, and further preferably 5.0 parts by mass or less, relative to 100.0 parts by mass of graphite particles.

[0063] The carbon content in the carbonaceous coated graphite particles is determined as follows.

[0064] First, the residual carbon ratio of the carbonaceous precursor (described later) is determined. The residual carbon ratio is the ratio of the residual amount to the charged amount (monomer: mass %) when the carbonaceous precursor is subjected to the same thermal history as the carbonaceous coated graphite particles to produce carbonaceous materials.

[0065] The carbon content can be determined from the determined residual carbon ratio of the carbonaceous precursor and the amount of the carbonaceous precursor added (described later).

[0066] For example, the amount of the carbonaceous precursor with a residual carbon ratio of "34 mass %" added is "8.0 mass parts" relative to 100.0 mass parts of graphite particles. In this case, the content of carbon in the obtained carbonaceous coated graphite particles is "2.7 mass parts" relative to 100.0 mass parts of graphite particles (=8.0×0.34).

[0067] Hereinafter, for convenience, the content of carbonaceous materials relative to 100.0 parts by mass of graphite particles may be simply referred to as “the content of carbonaceous materials”.

[0068] 〈Particle size〉

[0069] The particle size of the present carbonaceous coated graphite particles is preferably 5.0 μm or more, more preferably 6.5 μm or more. On the other hand, the particle size of the present carbonaceous coated graphite particles is preferably 15.0 μm or less, more preferably 12.0 μm or less.

[0070] The particle size is a median diameter at which the cumulative frequency of the particle size distribution determined using a laser diffraction particle size distribution analyzer (LMS2000e, manufactured by Seishin Enterprise Co., Ltd.) is 50% in terms of volume percentage.

[0071] [Method for producing carbonaceous coated graphite particles]

[0072] Next, a method for producing carbonaceous coated graphite particles according to the present embodiment (hereinafter also referred to as “the present production method”) will be described.

[0073] The present production method is a method for producing the present carbonaceous coated graphite particles described above. In summary, a carbonaceous precursor is attached to graphite particles, and then first calcination, intermediate exposure, and second calcination (hereinafter collectively referred to as "calcination") described below are sequentially performed.

[0074] Hereinafter, first, the graphite particles and the carbonaceous precursor used in the present production method will be described, and then each step in the present production method will be described.

[0075] 〈Graphite Particles〉

[0076] The method for producing the graphite particles used in the present production method is not particularly limited, and an example thereof includes a method of processing a raw material into a spherical shape.

[0077] Here, the raw material is graphite having a shape other than spherical (including ellipsoidal), for example, flaky graphite. The graphite may be either natural graphite or artificial graphite, but natural graphite is preferred because of its high crystallinity.

[0078] Specific examples of methods for processing the raw material into a spherical shape (method for spheronizing the raw material) include: a method of stirring the raw material in the presence of a granulation aid such as a binder or resin; a method of applying a mechanical external force to the raw material without using a granulation aid; a method of using both in combination, and the like.

[0079] Among them, a method of applying a mechanical external force to the raw material without using a granulation aid is preferred. This method will be described in more detail below.

[0080] More specifically, a raw material (for example, flaky graphite) is pulverized and granulated by applying a mechanical external force using a pulverizing device, thereby spheroidizing the raw material to obtain spheroidized graphite.

[0081] Examples of the pulverizing apparatus include a rotary ball mill, a counter jet mill (manufactured by Hosokawa Micron Co., Ltd.), a Current Jet (manufactured by Nisshin Engineering Co., Ltd.), a Hybridization System (manufactured by Nara Machinery Manufacturing Co., Ltd.), a CF pulverizer (manufactured by Ube Industries, Ltd.), a Mechano Fusion System (manufactured by Hosokawa Micron Co., Ltd.), and a THETA COMPOSER (manufactured by Tokuju Kosho Co., Ltd.). Among them, the Hybridization System (manufactured by Nara Machinery Manufacturing Co., Ltd.) is preferred.

[0082] In the present production method, it is preferred that a plurality of pulverizing devices are arranged in series and the raw material is continuously passed through the plurality of pulverizing devices. That is, it is preferred that the plurality of pulverizing devices are arranged in series so that the raw material is immediately pulverized and granulated in the next pulverizing device after passing through one pulverizing device.

[0083] In this case, the number of pulverizing devices is, for example, 2 or more, preferably 3 or more, more preferably 4 or more, further preferably 5 or more, particularly preferably 6 or more.

[0084] On the other hand, the number of pulverizing devices is preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less.

[0085] In one pulverizing device, the time for pulverizing and granulating the raw material (hereinafter also referred to as "pulverizing time") is preferably 8 minutes or more, more preferably 13 minutes or more, and even more preferably 18 minutes or more.

[0086] On the other hand, the pulverization time of one pulverization device is preferably 60 minutes or less, more preferably 50 minutes or less, and even more preferably 40 minutes or less.

[0087] The product of the number of pulverizing devices and the pulverizing time of one pulverizing device (hereinafter also referred to as "total pulverizing time") is preferably 30 minutes or more, more preferably 50 minutes or more, and even more preferably 90 minutes or more.

[0088] On the other hand, the total pulverization time is preferably 180 minutes or less, more preferably 160 minutes or less.

[0089] The pulverizing device usually has a built-in rotor.

[0090] The peripheral speed of the rotor in each pulverizing device is preferably 30 m / sec or more, more preferably 40 m / sec or more, and even more preferably 60 m / sec or more.

[0091] On the other hand, the peripheral speed of the rotor in each pulverizing device is preferably 100 m / sec or less, more preferably 80 m / sec or less.

[0092] In order to apply shearing force and compressive force to the raw material, the amount of the raw material filled in each pulverizing device is preferably small.

[0093] 〈Carbonaceous Precursor〉

[0094] The carbonaceous precursor is the precursor of the carbonaceous material described above, and is carbonized by the calcination described later to become the carbonaceous material covering the graphite particles.

[0095] Examples of the carbonaceous precursor include pitches and / or resins, which are carbon materials having lower crystallinity than graphite and which do not turn into graphite crystals even when subjected to a high-temperature treatment required for graphitization.

[0096] Examples of the asphalts include coal tar, tar light oil, tar medium oil, tar heavy oil, naphthalene oil, anthracene oil, coal tar pitch, asphalt oil, mesophase pitch, oxygen-crosslinked petroleum asphalt, and heavy oil.

[0097] Examples of the resins include polyvinyl alcohol, polyacrylic acid, phenol resin, furan resin, cellulose resin, polystyrene resin, polyimide resin, and epoxy resin.

[0098] From the viewpoint of the battery characteristics to be obtained, asphalts, phenolic resins, and the like are preferred.

[0099] In order to easily spread on the surface of graphite particles, the carbonaceous precursor is preferably in powder form. The median particle size (D 50 ) is not particularly limited, and is, for example, 1 to 50 μm.

[0100] 〈Preparation of Precursor-Attached Graphite Particles〉

[0101] In the present production method, first, a carbonaceous precursor is made to adhere to graphite particles, thereby obtaining precursor-adhered graphite particles in which the carbonaceous precursor adheres to at least a portion of the surface of the graphite particles.

[0102] As a method of making the carbonaceous precursor adhere to the graphite particles, a method of mixing the graphite particles and the carbonaceous precursor is mentioned, for example.

[0103] The mixing method is not particularly limited, and an example thereof includes a method of mixing graphite particles with a powdered or heated and melted carbonaceous precursor in a liquid state using a mixer or the like. In this case, a dispersion obtained by dispersing graphite particles in a dispersion medium may be used. Examples of the mixer include a pressure kneading machine, a double-roll mixer, and the like.

[0104] 《Amount of carbonaceous precursor added》

[0105] The amount of the carbonaceous precursor added (the amount of the carbonaceous precursor attached to the graphite particles) can be appropriately adjusted according to the desired amount of carbonaceous material to be finally obtained.

[0106] 〈Firing〉

[0107] Next, the obtained precursor-attached graphite particles are calcined (first calcination, intermediate exposure, and second calcination). Thus, the carbonaceous precursor is carbonized to form carbonaceous particles. Thus, carbonaceous-coated graphite particles in which at least a portion of the surface of the graphite particles is coated with carbonaceous particles are obtained.

[0108] At this time, by performing intermediate exposure in an oxidizing gas atmosphere between the first calcination performed in a non-oxidizing gas atmosphere and the second calcination performed in a non-oxidizing gas atmosphere, the crystallinity of the obtained carbonaceous material is improved.

[0109] 《First Firing》

[0110] In the first calcination, the precursor-adhered graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. (hereinafter also referred to as “first calcination temperature”) in a non-oxidizing gas atmosphere.

[0111] The reason why the gas atmosphere of the first firing is set to a non-oxidizing gas atmosphere is that carbonaceous materials burn and disappear in an oxidizing gas atmosphere.

[0112] Examples of the non-oxidizing gas atmosphere include nitrogen atmosphere, argon atmosphere, helium atmosphere, and vacuum atmosphere. The oxygen concentration of the gas atmosphere may be reduced by placing coke dust that oxidizes itself, thereby substantially providing a non-oxidizing gas atmosphere.

[0113] If the first calcination temperature is too low, the mass reduction start temperature of the obtained carbonaceous coated graphite particles decreases. Therefore, the first calcination temperature exceeds 900°C, preferably 950°C or higher, and more preferably 1000°C or higher.

[0114] On the other hand, if the first calcination temperature is too high, the mass reduction starting temperature of the obtained carbonaceous coated graphite particles becomes too high. Therefore, the first calcination temperature is 1500°C or lower, preferably 1400°C or lower, and more preferably 1250°C or lower.

[0115] The time for implementing the first calcination (the time for heating the precursor attached graphite particles at the first calcination temperature in a non-oxidizing gas atmosphere) is preferably 0.5 hours or more, more preferably 1 hour or more, and further preferably 2 hours or more. The upper limit is not particularly limited, for example, 30 hours, preferably 10 hours, and more preferably 5 hours.

[0116] The precursor-attached graphite particles after the first calcination are preferably cooled directly in the gas atmosphere of the first calcination (non-oxidizing gas atmosphere) to the intermediate exposure temperature described later.

[0117] "Intermediate Exposure"

[0118] In the intermediate exposure, the precursor-adhered graphite particles that have been subjected to the first calcination (and then cooled) are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C. (hereinafter also referred to as “intermediate exposure temperature”).

[0119] Examples of the oxidizing gas atmosphere include a gas atmosphere containing oxygen, ozone, and carbon dioxide, and an air atmosphere is preferred from the viewpoint of convenience.

[0120] If the intermediate exposure temperature is too low, the mass reduction starting temperature of the obtained carbonaceous coated graphite particles decreases. Therefore, the intermediate exposure temperature is 50° C. or higher, preferably 55° C. or higher, and more preferably 60° C. or higher.

[0121] On the other hand, if the intermediate exposure temperature is too high, the mass reduction starting temperature of the obtained carbonaceous coated graphite particles becomes too high. Therefore, the intermediate exposure temperature is 100°C or lower, preferably 90°C or lower, and more preferably 80°C or lower.

[0122] The time for implementing the intermediate exposure (the time for exposing the precursor-attached graphite particles to the oxidizing gas atmosphere at the intermediate exposure temperature) is preferably 10 minutes or more, more preferably 20 minutes or more, and further preferably 30 minutes or more. The upper limit is not particularly limited, for example, 120 minutes, preferably 90 minutes, and more preferably 60 minutes.

[0123] 《Second Firing》

[0124] In the second calcination, the precursor-adhered graphite particles subjected to the intermediate exposure are heated at a temperature of 1100° C. to 1500° C. (hereinafter also referred to as “second calcination temperature”) in a non-oxidizing gas atmosphere.

[0125] The reason why the gas atmosphere of the second calcination is a non-oxidizing gas atmosphere and the preferred example of the non-oxidizing gas atmosphere are the same as those of the first calcination.

[0126] If the second calcination temperature is too low, the mass reduction start temperature of the obtained carbonaceous coated graphite particles decreases. Therefore, the second calcination temperature is 1100° C. or higher, preferably 1150° C. or higher, and more preferably 1200° C. or higher.

[0127] It should be noted that the second calcination temperature is preferably a temperature equal to or higher than the first calcination temperature.

[0128] On the other hand, if the second calcination temperature is too high, the mass reduction starting temperature of the obtained carbonaceous coated graphite particles becomes too high. Therefore, the second calcination temperature is 1500°C or lower, preferably 1400°C or lower, and more preferably 1300°C or lower.

[0129] The time for implementing the second calcination (the time for heating the precursor attached graphite particles at the second calcination temperature in a non-oxidizing gas atmosphere) is preferably 0.5 hours or more, more preferably 1 hour or more, and further preferably 2 hours or more. The upper limit is not particularly limited, for example, 30 hours, preferably 10 hours, and more preferably 5 hours.

[0130] [Negative electrode for lithium-ion secondary battery (negative electrode)]

[0131] The negative electrode for lithium ion secondary battery of the present embodiment contains the above-mentioned carbonaceous coated graphite particles. Hereinafter, the "carbonaceous coated graphite particles" are sometimes referred to as "negative electrode materials". In addition, the negative electrode for lithium ion secondary battery is sometimes simply referred to as "negative electrode".

[0132] The negative electrode of this embodiment is produced in accordance with a common negative electrode.

[0133] When manufacturing the negative electrode, it is preferred to add a binder to the negative electrode material and use a previously prepared negative electrode mixture. The negative electrode mixture may contain an active material other than the negative electrode material and a conductive material.

[0134] The binder preferably exhibits chemical stability and electrochemical stability to the electrolyte. For example, fluorine-based resins such as polytetrafluoroethylene and polyvinylidene fluoride; resins such as polyethylene, polyvinyl alcohol, and styrene-butadiene rubber; and carboxymethyl cellulose can be used. Two or more of these can also be used in combination.

[0135] The binder is usually used in a ratio of about 1 to 20% by mass based on the total amount of the negative electrode mixture.

[0136] More specifically, first, the negative electrode material is adjusted to a desired particle size by arbitrarily classifying or the like. Then, the negative electrode material is mixed with a binder, and the obtained mixture is dispersed in a solvent to prepare a paste-like negative electrode mixture. Examples of the solvent include water, isopropanol, N-methylpyrrolidone, dimethylformamide, and the like. For mixing and dispersing, a known stirrer, mixer, kneader, and the like can be used.

[0137] The prepared paste is applied to one or both sides of the current collector and dried. The coating amount is preferably 3 to 15 mg / cm 2 , more preferably 5 to 15 mg / cm 2 Thus, a negative electrode mixture layer (negative electrode) that is uniformly and firmly bonded to the current collector can be obtained. The thickness of the negative electrode mixture layer is preferably 10 to 200 μm, and more preferably 20 to 100 μm.

[0138] By performing compression bonding such as pressing and pressing after the negative electrode mixture layer is formed, the adhesion strength between the negative electrode mixture layer (negative electrode) and the current collector can be further increased.

[0139] The shape of the current collector is not particularly limited, and may be, for example, foil, mesh, or mesh such as expanded metal. The material of the current collector is preferably copper, stainless steel, nickel, etc. The thickness of the current collector in the case of foil is preferably about 5 to 20 μm.

[0140] 〈Coating electrode density〉

[0141] In the negative electrode of this embodiment, the coating electrode density is preferably 1.10 g / cm 3 More preferably 1.20 g / cm 3 On the other hand, it is preferably 2.00 g / cm 3 Below, more preferably 1.90 g / cm 3 the following.

[0142] The coating electrode density of the negative electrode was determined as follows.

[0143] The mass (using an electronic balance) and thickness (using a micrometer) of the negative electrode punched into a certain area are measured. Next, the mass of 10 pieces of collectors punched into the same area are measured, and the average value is used as the mass of the collector. Further, the thickness of the collector is calculated based on the density of the metal of the collector. Then, the coated electrode density of the negative electrode is calculated by the following formula.

[0144] Negative electrode coating density = (negative electrode mass - collector mass) / (negative electrode thickness - collector thickness) × (punching area)

[0145] [Lithium-ion secondary battery]

[0146] The lithium ion secondary battery of the present embodiment includes the negative electrode of the present embodiment, and further includes a positive electrode, a nonaqueous electrolyte, and the like.

[0147] The lithium ion secondary battery of the present embodiment can be constructed by, for example, stacking a negative electrode, a nonaqueous electrolyte, and a positive electrode in this order and housing the stacked electrodes in an exterior material.

[0148] The form of the lithium ion secondary battery of the present embodiment can be arbitrarily selected from cylindrical, rectangular, coin, button, and the like depending on the application, the device on which it is mounted, the required charge and discharge capacity, and the like.

[0149] <positive electrode>

[0150] The positive electrode material (positive electrode active material) is preferably a material that can absorb / desorb a sufficient amount of lithium. In addition to lithium, the positive electrode active material may include lithium-containing transition metal oxides, transition metal sulfide compounds, vanadium oxides and lithium compounds thereof; X 6S 8-Y (wherein M is at least one transition metal element, X is a value in the range of 0≤X≤4, and Y is a value in the range of 0≤Y≤1) represented by Chevrel phase compounds; activated carbon; activated carbon fiber; etc. Vanadium oxides are represented by V2O5, V6O 13 , V2O4, V3O8.

[0151] The lithium-containing transition metal oxide is a composite oxide of lithium and a transition metal, and may be a composite oxide in which lithium and two or more transition metals are solid-dissolved. The composite oxide may be used alone or in combination of two or more.

[0152] Lithium-containing transition metal oxides are specifically LiM 1 1-X M 2 X O2(where M1 、M 2 is at least one transition metal element, X is a value in the range of 0≤X≤1), or LiM 1 1-Y M 2 Y O4 (where M 1 、M 2 is at least one transition metal element, and Y is a numerical value in the range of 0≤Y≤1).

[0153] M 1 、M 2 The transition metal element represented by is Co, Ni, Mn, Cr, Ti, V, Fe, Zn, Al, In, Sn, etc., preferably Co, Fe, Mn, Ti, Cr, V, Al, etc. Preferred specific examples are LiCoO2, LiNiO2, LiMnO2, LiNi 0.9 Co 0.1 O2、LiNi 0.5 Co 0.5 O2, etc.

[0154] Lithium-containing transition metal oxides can be obtained, for example, by using lithium and transition metal oxides, hydroxides, salts, etc. as starting materials, mixing these starting materials according to the composition of the desired metal oxide, and calcining them at 600 to 1000° C. in an oxygen atmosphere.

[0155] The positive electrode active material may be the above-mentioned compound alone or in combination of two or more. For example, carbon salts such as lithium carbonate may be added to the positive electrode. When forming the positive electrode, various additives such as existing known conductive agents and binders may be appropriately used.

[0156] The positive electrode can be produced, for example, by applying a positive electrode mixture composed of a positive electrode active material, a binder, and a conductive agent for imparting conductivity to the positive electrode on both surfaces of a current collector to form a positive electrode mixture layer.

[0157] As the binder, a binder used in the production of the negative electrode can be used.

[0158] As the conductive agent, known conductive agents such as graphite and carbon black can be used.

[0159] The shape of the current collector is not particularly limited, and examples thereof include foil and mesh. The material of the current collector is aluminum, stainless steel, nickel, etc. The thickness of the current collector is preferably 10 to 40 μm.

[0160] For the positive electrode, similarly to the negative electrode, a paste of positive electrode mixture may be applied to a current collector and dried, followed by compression bonding such as pressing.

[0161] 〈Non-aqueous electrolytes〉

[0162] The nonaqueous electrolyte may be a liquid nonaqueous electrolyte (nonaqueous electrolyte solution), or may be a polymer electrolyte such as a solid electrolyte or a gel electrolyte.

[0163] As the non-aqueous electrolyte, lithium salts such as LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5), LiCl, LiBr, LiCF3SO3, LiCH3SO3, LiN(CF3SO2)2, LiC(CF3SO2)3, LiN(CF3CH2OSO2)2, LiN(CF3CF2OSO2)2, LiN(HCF2CF2CH2OSO2)2, LiN((CF3)2CHOSO2)2, LiB[{C6H3(CF3)2}]4, LiAlCl4, and LiSiF6, which are electrolyte salts used in common non-aqueous electrolyte solutions, can be used. From the perspective of oxidation stability, LiPF6 and LiBF4 are preferred.

[0164] The concentration of the electrolyte salt in the nonaqueous electrolyte solution is preferably 0.1 to 5.0 mol / L, more preferably 0.5 to 3.0 mol / L.

[0165] Examples of the solvent used to prepare the non-aqueous electrolyte solution include carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, and diethyl carbonate; ethers such as 1,1- or 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, 1,3-dioxolane, 4-methyl-1,3-dioxolane, anisole, and diethyl ether; sulfides such as sulfolane and methyl sulfolane; nitriles such as acetonitrile, chloronitrile, and propionitrile; trimethyl borate, tetramethyl silicate, nitromethane, dimethylformamide, N-methylpyrrolidone, ethyl acetate, trimethyl orthoformate, nitrobenzene, benzoyl chloride, benzoyl bromide, tetrahydrothiophene, dimethyl sulfoxide, 3-methyl-2- Aprotic organic solvents such as oxazolidinone, ethylene glycol, dimethyl sulfite, etc.

[0166] When the nonaqueous electrolyte is a polymer electrolyte such as a solid electrolyte or a gel electrolyte, it is preferable to use a polymer gelled with a plasticizer (nonaqueous electrolyte solution) as a matrix.

[0167] As the polymer constituting the matrix, ether polymer compounds such as polyoxyethylene and crosslinked products thereof; poly(meth)acrylate polymer compounds; fluorine polymer compounds such as polyvinylidene fluoride and vinylidene fluoride-hexafluoropropylene copolymers, etc. can be suitably used.

[0168] The concentration of the electrolyte salt in the nonaqueous electrolyte solution as a plasticizer is preferably 0.1 to 5.0 mol / L, more preferably 0.5 to 2.0 mol / L.

[0169] In the polymer electrolyte, the proportion of the plasticizer is preferably 10 to 90% by mass, more preferably 30 to 80% by mass.

[0170] 〈Partition〉

[0171] A separator may also be used in the lithium ion secondary battery of this embodiment.

[0172] The material of the separator is not particularly limited, for example, woven fabric, nonwoven fabric, synthetic resin microporous film, etc. can be used. Among them, preferably a synthetic resin microporous film, wherein, from the aspect of thickness, film strength, and film resistance, a polyolefin microporous film is more preferably used. As the polyolefin microporous film, preferably a polyethylene microporous film, a polypropylene microporous film, a microporous film composited therefrom, etc. can be mentioned.

[0173] Example

[0174] Hereinafter, the present invention will be specifically described with reference to Examples. However, the present invention is not limited to the Examples described below.

[0175] <Example 1>

[0176] 《Preparation of graphite particles》

[0177] The flaky natural graphite (particle size: 8 μm) as a raw material was continuously passed through four pulverizing devices (Hybridization System, manufactured by Nara Machinery Manufacturing Co., Ltd.) arranged in series. In each pulverizing device, the pulverizing time was set to 10 minutes and the circumferential speed of the rotor was set to 60 m / s. Thus, graphite particles as spherical graphite were obtained by pulverizing and granulating the raw material.

[0178] 《Preparation of Precursor-Attached Graphite Particles》

[0179] The phenolic resin, i.e., the carbonaceous precursor, which was pulverized into powder using a hammer mill was added to the obtained graphite particles (spheroidized graphite), and mixed for 15 minutes at 25° C. using a drum mixer. Thus, precursor-attached graphite particles were obtained in which the carbonaceous precursor (phenolic resin) was attached to the surface of the graphite particles (spheroidized graphite).

[0180] 《Preparation of Carbon-Coated Graphite Particles》

[0181] Next, the obtained precursor-attached graphite particles were placed in a graphite container with a lid, and calcined (first calcination, intermediate exposure, and second calcination) using a tubular furnace.

[0182] Specifically, first, in the first sintering, a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen flows at 2 L / min is set, and then the precursor-attached graphite particles are heated at a first sintering temperature of 1100° C. for 60 minutes, and then cooled to the intermediate exposure temperature described later without changing the gas atmosphere.

[0183] Next, in the intermediate exposure, the cooled precursor-attached graphite particles were exposed to an air atmosphere (oxidative gas atmosphere) at an intermediate exposure temperature of 70° C. for 30 minutes.

[0184] Then, in the second calcination, after setting the gas atmosphere to flow nitrogen at 2 L / min (non-oxidizing gas atmosphere), the precursor-attached graphite particles were heated at the second calcination temperature of 1100° C. for 60 minutes.

[0185] As a result, the carbonaceous precursor (phenol resin) becomes carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) are coated with carbonaceous are obtained.

[0186] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0187] The Making of Negative Electrode

[0188] 98 parts by mass of carbonaceous coated graphite particles (negative electrode material), 1 part by mass of carboxymethyl cellulose (binder), and 1 part by mass of styrene-butadiene rubber (binder) were added to water and stirred to prepare a negative electrode mixture paste.

[0189] The prepared negative electrode mixture paste is applied to the copper foil with a uniform thickness, and further dried at 90°C in a vacuum to form a negative electrode mixture layer. Next, the negative electrode mixture layer is pressurized with a pressure of 120MPa using a manual press. Then, the copper foil and the negative electrode mixture layer are punched into a circular shape with a diameter of 15.5mm. In this way, a negative electrode (coating electrode density: 1.50g / cm 3 ).

[0190] The Making of Positive Electrode

[0191] A positive electrode composed of LiCoO2 (93 mass %), a conductive agent (4 mass %) and a binder (3 mass %) was used. Graphite flake particles were used as the conductive agent, and styrene-butadiene rubber was used as the binder.

[0192] 《Evaluating the production of batteries》

[0193] As an evaluation battery, Figure 1 The button-type secondary battery shown.

[0194] Figure 1 is a cross-sectional view showing a button-type secondary battery. Figure 1 In the button-type secondary battery shown, the outer cup 1 and the outer can 3 are riveted to form a sealed structure with an insulating gasket 6 interposed therebetween. Inside the sealed structure, the collector 7a, the positive electrode 4, the separator 5, the negative electrode 2, and the collector 7b are stacked in order from the inner surface of the outer can 3 to the inner surface of the outer cup 1.

[0195] The following was produced Figure 1 The button-type secondary battery shown.

[0196] First, LiPF6 was dissolved in a mixed solvent of ethylene carbonate (33% by volume) and ethyl methyl carbonate (67% by volume) at a concentration of 1 mol / L to prepare a non-aqueous electrolyte solution. A separator 5 impregnated with the non-aqueous electrolyte solution was prepared by impregnating the obtained non-aqueous electrolyte solution into a polypropylene porous body (thickness: 20 μm).

[0197] Next, the prepared separator 5 is sandwiched between the negative electrode 2 which is closely attached to the current collector 7b made of copper foil and the positive electrode 4 which is closely attached to the current collector 7a made of nickel mesh, and the layers are stacked. Then, the current collector 7b and the negative electrode 2 are accommodated in the outer cup 1, the current collector 7a and the positive electrode 4 are accommodated in the outer can 3, and the outer cup 1 and the outer can 3 are joined. Furthermore, the outer cup 1 and the outer can 3 are sealed by riveting the peripheral portions thereof with the insulating gasket 6 interposed therebetween. Thus, a button-type secondary battery is manufactured.

[0198] The produced button-type secondary battery (evaluation battery) was used to carry out the test described below to evaluate the battery characteristics. The results are shown in Table 1 below.

[0199] In the following tests, the process of absorbing lithium ions into the negative electrode material is called charging, and the process of desorbing lithium ions from the negative electrode material is called discharging.

[0200] 《Test 1: Output Characteristics》

[0201] After constant current charging at a current value of 0.1C until the circuit voltage reaches 1mV, switch to constant voltage charging and continue charging until the current value reaches 20μA. The charging capacity (single cell: mAh) is calculated based on the amount of power supplied during this period. Then, stop for 10 minutes. Next, constant current discharge is performed at a current value of 0.2C until the circuit voltage reaches 1.5V. The initial discharge capacity (single cell: mAh) is calculated based on the amount of power supplied during this period.

[0202] Next, constant current charging was performed at a current value of 0.1C until the circuit voltage reached 1mV, and then constant voltage charging was switched to continue charging until the current value reached 20μA. Then, a 10-minute rest period was performed, and then constant current discharge was performed at a current value of 2.0C until the circuit voltage reached 1.5V. The rapid discharge capacity (single cell: mAh) was calculated based on the amount of electricity passed during this period.

[0203] From the obtained discharge capacity, the output characteristics (monomer: %) were determined based on the following formula.

[0204] Output characteristics = 100 × (fast discharge capacity / initial discharge capacity)

[0205] 《Test 2: Fast Charging Characteristics》

[0206] After constant current charging at a current value of 0.1C until the circuit voltage reaches 1mV, switch to constant voltage charging and continue charging until the current value reaches 20μA. The charging capacity (single cell: mAh) is calculated based on the amount of power supplied during this period. Then, stop for 10 minutes. Next, constant current discharge is performed at a current value of 0.2C until the circuit voltage reaches 1.5V. The initial discharge capacity (single cell: mAh) is calculated based on the amount of power supplied during this period.

[0207] Next, constant current discharge was performed at a current value of 2.0 C until the circuit voltage reached 1.5 V. The rapid charge capacity (unit: mAh) was calculated from the amount of current flow during this period.

[0208] From the obtained charge capacity, the rapid charge characteristic (single body: %) was determined based on the following formula.

[0209] Fast charge characteristic = 100 × (fast charge capacity / initial discharge capacity)

[0210] 《Test 3: Cyclic Characteristics》

[0211] After constant current charging at a current value of 0.1C until the circuit voltage reaches 1mV, switch to constant voltage charging and continue charging until the current value reaches 20μA. The charging capacity (single cell: mAh) is calculated based on the amount of power supplied during this period. Then, stop for 10 minutes. Next, constant current discharge is performed at a current value of 0.2C until the circuit voltage reaches 1.5V. The discharge capacity (single cell: mAh) is calculated based on the amount of power supplied during this period.

[0212] This charge and discharge was repeated 10 times (from the 1st cycle to the 10th cycle), and the cycle characteristics (monomer: %) were calculated based on the following formula from the obtained discharge capacity.

[0213] Cycle characteristics = 100 × (discharge capacity at the 10th cycle / discharge capacity at the 1st cycle)

[0214] <Example 2>

[0215] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the second calcination temperature was changed to 1200° C. The results are shown in Table 1 below.

[0216] <Example 3>

[0217] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the time for performing the intermediate exposure was changed to 10 minutes. The results are shown in Table 1 below.

[0218] <Example 4>

[0219] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the carbonaceous content was changed to 1.0 part by mass. The results are shown in Table 1 below.

[0220] <Example 5>

[0221] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the carbonaceous content was changed to 10.0. The results are shown in Table 1 below.

[0222] <Example 6>

[0223] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1, except that the carbonaceous precursor was changed from phenolic resin to coal tar. The results are shown in Table 1 below.

[0224] <Comparative Example 1>

[0225] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the first calcination temperature was changed to 800° C. The results are shown in Table 1 below.

[0226] <Comparative Example 2>

[0227] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1, except that the intermediate exposure and the second calcination were not performed. The results are shown in Table 1 below.

[0228] <Comparative Example 3>

[0229] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the second calcination temperature was changed to 1000° C. The results are shown in Table 1 below.

[0230] <Comparative Example 4>

[0231] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the first calcination temperature was changed to 1600° C. The results are shown in Table 1 below.

[0232] <Comparative Example 5>

[0233] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the carbonaceous content was changed to 0.04 parts by mass. The results are shown in Table 1 below.

[0234] <Comparative Example 6>

[0235] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the carbonaceous content was changed to 16.0 parts by mass. The results are shown in Table 1 below.

[0236] <Comparative Example 7>

[0237] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the intermediate exposure temperature was changed to 30° C. The results are shown in Table 1 below.

[0238] <Comparative Example 8>

[0239] Carbonaceous coated graphite particles were prepared and evaluated in the same manner as in Example 1 except that the intermediate exposure temperature was changed to 150° C. The results are shown in Table 1 below.

[0240] <Comparative Example 9>

[0241] 《Preparation of graphite particles》

[0242] In the same manner as in Example 1, graphite particles as spheroidized graphite were obtained.

[0243] 《Preparation of Precursor-Attached Graphite Particles》

[0244] Precursor-attached graphite particles in which a carbonaceous precursor (phenol resin) was attached to the surface of graphite particles (spheroidized graphite) were obtained in the same manner as in Example 1 so that the carbonaceous content in the finally obtained carbonaceous coated graphite particles was 5.0 parts by mass.

[0245] 《Preparation of Carbon-Coated Graphite Particles》

[0246] The obtained precursor-adhered graphite particles were placed in a graphite container with a lid and fired using a tubular furnace.

[0247] Specifically, first, the first calcination was carried out in the same manner as in Example 1.

[0248] Next, intermediate exposure was carried out in the same manner as in Example 1 except that the intermediate exposure temperature was changed to 80° C., thereby obtaining an intermediate exposure body.

[0249] Then, the second carbonaceous precursor was attached. More specifically, the phenolic resin was attached to the intermediate exposure body under the same conditions as in the "Preparation of Precursor-Attached Graphite Particles" of Example 1. At this time, the phenolic resin was attached in such a manner that the carbon content in the finally obtained carbonaceous coated graphite particles reached 5.0 parts by mass.

[0250] Finally, the second calcination was carried out in the same manner as in Example 1.

[0251] Thus, the carbonaceous precursor (phenol resin) became carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) were coated with carbonaceous were obtained. The carbonaceous content in the obtained carbonaceous-coated graphite particles was 10.0 parts by mass.

[0252] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0253] <Comparative Example 10>

[0254] 《Preparation of graphite particles》

[0255] In the same manner as in Example 1, graphite particles as spheroidized graphite were obtained.

[0256] 《Preparation of Precursor-Attached Graphite Particles》

[0257] In the same manner as in Example 1, precursor-attached graphite particles were obtained.

[0258] 《Preparation of Carbon-Coated Graphite Particles》

[0259] The obtained precursor-adhered graphite particles were placed in a graphite container with a lid and fired using a tubular furnace.

[0260] Specifically, first, a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen was flowed at 2 L / min was set, and then the precursor-attached graphite particles were heated at a first calcination temperature of 700° C. for 60 minutes.

[0261] Next, without cooling (intermediate exposure), heating was performed at a second calcination temperature of 1300° C. for 60 minutes in a gas atmosphere (non-oxidizing gas atmosphere) in which nitrogen was flowed at 2 L / min.

[0262] As a result, the carbonaceous precursor (phenol resin) becomes carbonaceous, and carbonaceous-coated graphite particles in which the surfaces of graphite particles (spheroidized graphite) are coated with carbonaceous are obtained.

[0263] The physical properties of the obtained carbonaceous coated graphite particles were determined by the above-mentioned methods. The results are shown in Table 1 below.

[0264]

[0265] 〈Summary of evaluation results〉

[0266] As shown in Table 1, compared with Comparative Examples 1 to 4 and 7 to 8 outside the mass reduction start temperature range of 800 to 980°C, Examples 1 to 6 having a mass reduction start temperature within the range of 800 to 980°C have good output characteristics, rapid charge characteristics, and cycle characteristics.

[0267] Comparative Example 5, in which the carbonaceous content was less than 0.1 parts by mass, had insufficient cycle characteristics.

[0268] Comparative Example 6, in which the carbon content exceeded 15.0 parts by mass, had insufficient output characteristics and rapid charging characteristics.

[0269] In Comparative Example 9 in which the second deposition of the carbonaceous precursor was performed after the intermediate exposure, the mass reduction starting temperature was lower than 800° C., and the output characteristics and the rapid charging characteristics were insufficient.

[0270] In Comparative Example 10 in which only the first calcination and the second calcination were performed without intermediate exposure, the mass reduction starting temperature exceeded 980° C., and the output characteristics, rapid charge characteristics, and cycle characteristics were insufficient.

Claims

1. A carbonaceous coated graphite particle, comprising: Graphite particles, and a carbonaceous material covering at least a portion of the surface of the graphite particle, The mass reduction starting temperature when heated in a water vapor atmosphere is 800 to 980°C. The content of the carbonaceous material is 0.1 to 15.0 parts by mass relative to 100.0 parts by mass of the graphite particles. 2 . The carbonaceous coated graphite particles according to claim 1 , which are negative electrode materials for lithium ion secondary batteries.

3. A negative electrode for a lithium ion secondary battery, comprising the carbonaceous coated graphite particles according to claim 1. 4 . A lithium ion secondary battery comprising the negative electrode according to claim 3 .

5. A method for producing carbonaceous coated graphite particles, which is a method for producing the carbonaceous coated graphite particles according to claim 1, the method comprising: making a carbonaceous precursor, which is a precursor of the carbonaceous material, adhere to the graphite particles to obtain precursor-attached graphite particles, A first calcination step is performed in which the precursor-attached graphite particles are heated at a temperature exceeding 900° C. and not more than 1500° C. in a non-oxidizing gas atmosphere. After the first calcination, an intermediate exposure is performed in which the precursor-attached graphite particles are exposed to an oxidizing gas atmosphere at a temperature of 50 to 100° C., After the intermediate exposure, a second calcination is performed in which the precursor-attached graphite particles are heated at a temperature of 1100 to 1500° C. in a non-oxidizing gas atmosphere.

Citation Information

Patent Citations

  • Method for producing graphite particles coated with carbonaceous film

    WO2021260964A1